The Effect of Temperature and Roasting Duration on Physical Characteristics and Sensory Quality Of Singgalang Arabica Coffee (Coffea arabica) Agam Regency - Rince Alfia Fadri; Kesuma Sayuti; Novizar Nazir; Irfan Suliansyah (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2019)
The purpose of this study were to determine the effect of temperature and roasting duration on physical characteristics and quality of arabica coffee sensory,: find out the best temperature and roasting duration treatmen to physical characteristics and quality of arabica coffee sensory. This study used a factorial complete randomized design with two factors (200°C, 220°C and 240°C) and duration of roasting (12, 15, and 18 minutes). The variables observed in this study were rendemen (sucrose content of sugar cane crop or sample), water content, color value, acidity and sensory test of arabica coffee. The results showed that temperature and duration of roasting had effect on rendemen, water content, color value, acidity, flavor, taste and color of arabica coffee. The temperature of 220 ° C with 12 minutes of roasting is produceed the best physical characteristics and sensory quality of Singgalang arabica coffee, with 88.1% of rendemen, 1.23% of water content (bb), different color L (Lightness) 6,07, acidity 5.81, scent score 3.5), taste score value of 3.2, color score 3.6.